Comparison of propofol-esketamine versus propofol for anesthesia in gastroscopy: a double-blind, randomized controlled clinical trial - Liu, Xiaoli; Xiao, Qingyu; Zhuang, Shaohui (Frontiers in Medicine, 2023)
Objective: To compare the effects of propofol-esketamine and propofol in gastroscopy in adults.Methods: This randomized controlled clinical trial was performed from January 2021 to March 2021.Eighty patients were enrolled and allocated into normal saline group (group N) and esketamine group (group E). The primary outcome was total amount of propofol. Secondary outcomes included incidences of injection pain, involuntary movement, hemodynamic and respiratory adverse events during examination, total examination time, recovery time and postoperative adverse effects.Results: Total amount of propofol was significantly smaller in group E (101.64±32.64 mg) than in group N (129.55±36.34 mg, P=0.001). Incidences of injection pain, involuntary movement and hypotension was significantly lower in group E than in group N. Incidences of hypertension and tachycardia was higher in group E than in group N. There was no significant difference in incidences of laryngospasm or hypoxemia, total examination time, recovery time, incidences of postoperative adverse effects between two groups.Conclusions: Combination of propofol with 0.2mg/kg esketamine reduced total amount of propofol, provided a more stable hemodynamic status and did not affect recovery time in gastroscopy.